Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

The conservation of a gender fantasy: Women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
Cette thèse fait l'analyse de la radio anglophone « Top 40 » à Montréal, en mettant l'accent sur la sexospécificité des animateurs et des auditeurs. En étudiant l'histoire de la radio commerciale, et les liens entre la radio et les femmes, ce travail démontre que les postes de radio ne faisaient pas plus que maintenant une programmation basée sur une compréhension réelle de leurs auditeurs, mais plutôt sur une idée virtuelle de leur auditoire-cible. Ceci traduit une manière conservatrice d'imaginer un auditoire féminin et une programmation qui ne respecte pas réellement les vrais intérêts des femmes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; communication; culture populaire; discipline; discours dominant; genre; montréal; mémoires/thèses; périodes historiques; radio; ressource en ligne; régions géographiques; sexisme; stéréotypes de genre; systèmes d'oppressions